Compulsive smartphone usage and users' ill-being among young Indians: Does personality matter?. Issue 5 (August 2018) - Panda, Abinash; Jain, Nikunj Kumar
Highlights: Extraversion and conscientiousness positively influence compulsive smartphone usage. Neuroticism negatively influences compulsive smartphone usage. Openness and agreeableness negatively influence compulsive smartphone usage. Compulsive smartphone usage negatively affects emotional and physical health. Abstract: Personality characteristics are found to have significant influence on the extent of smartphone usage among the Indian youth. Compulsive usage of smartphones, however, affects the users' emotional and physical health. The objective of this study is to examine how personality characteristics are related to compulsive smartphone usage and if compulsive smartphone usage impacts users' ill being. Personality characteristics such as extraversion and conscientiousness are found to be leading to the compulsive smartphone usage, whereas neuroticism, openness to new experience, and agreeableness are found to be negatively influencing compulsive smartphone usage. Extraversion is found to have maximum influence on an individual's compulsive tendency to use smartphone, followed by conscientiousness. The findings of this study also made the authors believe that compulsive smartphone usage, affects both emotional (affecting inter-personal and family relationships) and physical (lack of quality sleep and physical discomfort) health of the smartphone users. Emotional health, however, is found to be more affected by compulsive smartphone usage compared to physical health. Given these findings, it is desirable that youths in Indian should be appropriately guided to use smartphones judiciously so that they do not end up being the victims of compulsive usage and subsequently addiction.